Tuberculosis of the Oral Cavity Misdiagnosed as Precancerous Lesion - Vanja Vučićević Boras; Dragana Gabrić; Ljiljana Smiljanić Tomičević; Sven Seiwerth; Krešimir Gršić; Božena Šarčević; Božena Lončar Brzak; Emilija Marunica; Ana Glavina (University of Zagreb. School of Dental Medicine, 2017)
Introduction: The aim of this case report was to discuss an extremely rare oral lesion as a result of primary pulmonary tuberculosis. Case report: In this case report, the patient with refractory painless ulceration at ventral surface of the tongue was described. Detailed medical history was taken followed by clinical examination of the oral mucosa and palpation of regional lymph nodes. Clinical examination revealed ulceration on the patient's ventro-lateral surface of the tongue, approximately two centimeters in diameter. Palpation of regional lymph nodes has not revealed enlargement. The toluidine blue test of the suspected lesion was performed at each control examination. Biopsy samples for histopathologic diagnosis were taken three times. The analysis of the first biopsy sample for histopathology revealed a non-specific inflammation, the second biopsy revealed a caseous necrosis without positive Ziehl-Neelsen staining and the third biopsy revealed a granulomatous inflammation which was highly suspicious of sarcoidosis. During hospitalization, the patient underwent a complete physical examination, and laboratory and radiological diagnostics. Physical chest examination revealed bilaterally coarse crepitations and laboratory findings of his complete blood count revealed normocytic anemia of chronic disease. Radiographic examination of lungs showed multiple small nodules bilaterally and positive direct sputum smear. Conclusion: Although oral tuberculosis is a rare condition, it must be taken into account in differential diagnosis of refractory painless oral ulcers.